Optimalisasi Platform Digital Dalam Pembelajaran Daring Di Tengah Pandemi COVID-19 - Ferdi Arifin; Elita Ulfiana; Wihadi Admojo (LPPM Universitas Terbuka, 2020)
Global pandemic forces teachers and students for studying from home. Many platforms can be used for substituting offline learning to online learning. Optimalization digital learning platform is one of ways to adjust learning activities in the pandemic. This article aims to elaborate optimalization digital platform for online learning among teachers in Abi Ummi school. The research uses qualitative and netnography approach for understanding how to optimize online learning in the pandemic. The result shows that social media can be one of digital platform for online learning. The most digital platfom used by Abi Ummi teachers are Google Classrom as learning management system, Youtube and Instagram as material contents shared, and Whatsapp and Telegram as media messengers for discussing the material.